Pathogenicity of indigenous soil isolate of Bacillus thuringiensis to Helicoverpa armigera Hübner 1809 (Lepidoptera: Noctuidae) - Muhammad Zeeshan Majeed; Muhammad Asam Riaz; Muneeba Arif Khan; Chun-Sen Ma; Salman Ahmad (Egyptian Journal of Biological Pest Control, 2018)
Abstract This study evaluated the pathogenicity of indigenous soil isolate of Bacillus thuringiensis (Bt) strains, applied without and along with 1.0% MgCl2 salt, to Helicoverpa armigera Hübner (Lepidoptera: Noctuidae). Toxicity and effect of Bt isolate on larval development (weight) were assessed using in vitro bioassays. Six concentrations of the tested Bt with salt (i.e., 1.0 × 107, 0.5 ×  105, 1.0 × 105, 1.5 × 105, and 2.0 × 105 cfu/ml), five without salt (i.e., 0.5 × 105, 1.0 × 105, 1.5 × 105, and 2.0 × 105 cfu/ml), and control were bioassayed against third-instar larvae of H. armigera under a complete randomized design (CRD), with four replications. Results revealed that both larval mortality and weight changes were significantly affected by time (F 5, 19 = 35.98; P <  0.001 and F 5, 19 = 11.01; P < 0.001, respectively) and treatments (F 5, 19 = 27.45; P < 0.001 and F 5, 19 = 25.07; P < 0.001). The highest larval mortality (91.1%) was exhibited by the highest concentration (1.0 × 107 cfu/ml), followed by 2.0 × 105 cfu/ml concentration, without salt (88.9%) and with salt (66.7%). Median lethal concentration (LC50) values of isolated Bt strain were 1.7 and 1.27 × 105 cfu/ml, without salt, and 1.80 and 1.13 × 105 cfu/ml, with salt, at 96 and 120 h, respectively. Regarding the impact of Bt isolate on larval development, treatment with the highest concentration (1.0 × 107 cfu/ml) had the most significant and negative impact on larval weight change (R 2 = 0.53), followed by 2.0 × 105 cfu/ml Bt concentration (R 2 = 0.40). There was no obvious synergistic or additive effect, but rather an inhibition was observed on the pathogenicity potential or larvicidal effect of Bt isolate.